2021
DOI: 10.3390/en14185701
|View full text |Cite
|
Sign up to set email alerts
|

The Bees Algorithm Tuned Sliding Mode Control for Load Frequency Control in Two-Area Power System

Abstract: This paper proposes a design of Sliding Mode Control (SMC) for Load Frequency Control (LFC) in a two-area electrical power system. The mathematical model design of the SMC is derived based on the parameters of the investigated system. In order to achieve the optimal use of the proposed controller, an optimisation tool called the Bees Algorithm (BA) is suggested in this work to tune the parameters of the SMC. The dynamic performance of the power system with SMC employed for LFC is studied by applying a load dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Several researchers optimally tuned the proposed controller (SMC, ASTSMC, ISMC, …., etc.) by an optimization algorithm such as Hybridized gravitational search algorithm, Artificial Bee Colony, and Bees Algorithm [16][17][18]. In ref.…”
Section: Literature Surveymentioning
confidence: 99%
“…Several researchers optimally tuned the proposed controller (SMC, ASTSMC, ISMC, …., etc.) by an optimization algorithm such as Hybridized gravitational search algorithm, Artificial Bee Colony, and Bees Algorithm [16][17][18]. In ref.…”
Section: Literature Surveymentioning
confidence: 99%
“…Shouran et al [21] in their paper suggested a Sliding Mode Control (SMC) concept for Load Frequency Control (LFC) in a two-area electrical power system. Depending on the researched system's properties, the mathematical model design for the SMC is generated.…”
Section: Literature Surveymentioning
confidence: 99%
“…Currently, rising energy demand and the depletion of fossil fuel resources have necessitated the extensive use of Renewable Energy (RE), which is considered clean and cost-effective, and likely to be connected to interconnected power systems for distributed utilization [1]. The integration of RE such as solar and wind leads to an uncertain variation in the generation of power due to the intermittent nature of RE, which introduces frequency oscillation that leads to multiple protection relays trip in the power system [2]. Automatic Load Frequency Control (ALFC) has proven very effective in regulating the system frequency by adjusting the generation system.…”
Section: Introductionmentioning
confidence: 99%